FEMINISTIC APPROACH AND SOCIAL ISSUES IN CHETAN BHAGAT‘s SELECT NOVELS - E. , TITUS LIVINGSTON; M. , RAKESH BABU (International Journal of Psychosocial Rehabilitation, 2020)
Chetan Bhagat is one of the young Indian authors who has questioned the social issues prevailing in society. All his novels are framed in a way of motivating the youngsters. The purpose of the study is to deal with Chetan Bhagat’s selected novels regarding the social, religious, and traditional empowerment of women. The present generation wants to tackle the constructive ideas framed in the past, but they fall prey to their own family. A clear comparison between modern and traditional women is discussed. The study shows how the modern woman empowers herself even when the constructive idea is flourished in the modern era. The study ends with the advice provoked by Chetan Bhagat for the youngsters. He states only the youngsters can rectify the social issues with coordination and friendship.